(untitled) (The Conference Hub, 2025)
This thesis presents a retrospective epidemiological analysis of COVID-19 infection incidence in Tashkent city from 2020 to 2023 and the first half of 2024. The study investigates the dynamics of infection spread across various districts of Tashkent city and identifies factors influencing the spread of the disease. The results indicate that infection rates significantly differ between districts, with some periods showing higher rates of infection.